A comparative study of Sargassum species from the Yucatan Peninsula coast: morphological and chemical characterisation. Issue 3 (3rd May 2020) - Rosado-Espinosa, Luis Alberto; Freile-Pelegrín, Yolanda; Hernández-Nuñez, Emanuel; Robledo, Daniel
ABSTRACT: Several species of Sargassum have been reported from the Yucatan peninsula coast, many of which end up as beach cast material, accumulating on the coast during colder months. The phenotypic plasticity of Sargassum makes specimen identification difficult. Two approaches were used in the current study to corroborate identification of the most abundant species: traditional taxonomic characters, and chemical characterisation. Fresh material from eight species of Sargassum was collected on the Yucatan coast. Specimens were identified using the following morphological features: cryptostomata, blade shape and size, and the shape of floating vesicles. Two cell wall polysaccharides, alginate and fucoidan, were extracted, quantified, and characterised from five of the eight species collected. Organic extracts were prepared and GC–MS analyses were performed on the three most abundant species, looking for species-specific compounds. Our analysis identified different chemical constituents depending on the solvent used. In the dichloromethane fraction, hexanoic acid, 2-ethyl was obtained from S. buxifolium whereas benzyl benzoate and epistephamiersine were found in S. hystrix . For the latter species, cholesta-4, 6-dien-3-ol, (á)- was found in the hexane fraction, whereas 2, 2ʹ-ethyldenebis(4, 6- di-tert-butylphenol) and 2-pentadecanone, 6, 10, 14-trimethyl- were present in S. fluitans . We discuss the applicability and usefulness of this method to assist taxonomic identification of Sargassum species.